Impact of Opioid and Nonopioid Drugs on Postsurgical Pain Management in the Rat - Wilson, Natalie M. (Pain Res Treat, 2016)
Aim. Nonsteroidal anti-inflammatory drugs or opioids are commonly used to control surgical pain following veterinary and clinical procedures. This study evaluated the efficacy of postoperative ketorolac or buprenorphine following abdominal surgery. Main Methods. Mean arterial pressure (MAP), heart rate, animal activity, corticosterone levels, and a nociceptive sensitivity assay were used to evaluate 18 adult male Sprague-Dawley rats which underwent aortic artery occlusion for implantation of a radiotelemetry device. The animals were treated postoperatively with intraperitoneal injections of vehicle, ketorolac (10 mg/kg), or buprenorphine (0.06 mg/kg) every 8 hours for 3 days. Key Findings. There were no consistent significant changes in any of the telemetry parameters after treatment with ketorolac compared with no saline treatment with the exception of increased MAP in the buprenorphine group during the first 48 hours when compared with other treatment groups. There was a sustained increase in fecal corticosterone levels from baseline on days 2–7 with buprenorphine compared with vehicle- or ketorolac-treated animals. All treatment conditions displayed reduced paw withdrawal thresholds (PWTs) from day 1 to day 21 following surgery. Compared with the vehicle treatment group, buprenorphine-treated animals exhibited significantly lower PWT levels from day 4 to 14 days. Significance. Given the prolonged increase in fecal corticosterone levels and pronounced changes in tactile hyperalgesia behavior in rodents subjected to buprenorphine treatment, these data suggest that ketorolac may be superior to buprenorphine for the treatment of postprocedure pain behavior in rodents.